Synthesis of two series of novel sulfonyl hydrazones and assessment of their antioxidant and anti-obesity activities using in vitro and in silico approaches - Basaran, Eyup; Bursal, Ercan; Yetissin, Fuat; Cakmak, Resit; Korkmaz, Adem (Elsevier, 2026)
Combating obesity is an urgent priority, as it significantly impacts both the global economy and public health. Inhibition of pancreatic lipase (PL) enzyme has been accepted to be one of the most effective therapeutics in obesity management. In this study, starting from 2,5-dimethoxybenzenesulfonyl chloride (DMBSC), two series of novel N-aryl sulfonyl hydrazone derivatives (14-19 and 20-25) carrying sulfonate moieties were designed and synthesized successfully. The chemical structures of the target molecules were identified and characterized using various spectroscopic techniques (FT-IR, 1H and 13C NMR) and elemental analyses. In addition, their antioxidant and antiobesity potentials were examined using in vitro methods and in silico techniques, such as molecular docking, ADME/drug likeness predictions, and toxicity analysis. The tested compounds demonstrated significant PL inhibitory activity in an in vitro enzyme assay. Remarkably, compounds 21 (IC50 = 46.53+6.67 & micro;M), 14 (IC50 = 50.46+10.48 & micro;M), and 20 (IC50 = 54.14+29.23 & micro;M) exhibited superior inhibitory potency compared to the reference standard, orlistat (IC50 = 45.12+13.51 & micro;M). Molecular docking studies were performed to explore the binding interactions between the most active compounds and PL. The compounds 21, 14, 20, and standard orlistat showed-8.5 kcal/mol,-8.3 kcal/mol,-8.2 kcal/mol, and-7.1 kcal/mol affinity energy values, respectively. This study reports the potential of sulfonyl hydrazone derivatives as a promising new class of pancreatic lipase inhibitors (PLIs) with antioxidant activity.
Keywords: Aryl Sulfonate; N -Aryl Sulfonyl Hydrazone; Antioxidant; Pancreatic Lipase; Molecular Docking